2022
DOI: 10.5812/jhealthscope-122047
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Framework for Attracting Public Participation in the Iranian Health System: A Comparative and Mixed-Method Study

Abstract: Background: Public participation strengthens the public presence in healthcare. Objectives: This study aimed to determine the dimensions of attracting public participation in the Iranian health system. Methods: A mixed-method research was conducted from May 2019 to July 2020. A comparative study (using the documents of five countries that were selected purposefully), tool design and validation (through holding two expert panels with the participation of 26 people who were selected based on the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In confirmation of this finding, a study by Dejman et al raised the lack of a suitable structure for the management of grassroots at the level of the Ministry of Health and some other institutions as an important issue in organizing community participation by all managers and founders of the program [ 43 ]. Various studies have reported the effective factors in appealing to public participation in the health system such as the existence of a specific structure for attracting community participation in the health system [ 44 , 45 ]. Having the proper organizational structure for participation is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In confirmation of this finding, a study by Dejman et al raised the lack of a suitable structure for the management of grassroots at the level of the Ministry of Health and some other institutions as an important issue in organizing community participation by all managers and founders of the program [ 43 ]. Various studies have reported the effective factors in appealing to public participation in the health system such as the existence of a specific structure for attracting community participation in the health system [ 44 , 45 ]. Having the proper organizational structure for participation is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Another obstacle to public participation is a lack of the community’s role in developing plans and programs. In this regard, participants in the study of Dejman et al have expressed the lack of public participation in the decision-making process at high levels in community-based governmental programs to be one of the important obstacles [ 44 ]. Considering the fundamental role of community participation in all administrative levels of the health system, creating formal organizational structures for this purpose can act as a basis for the existence of systemic thinking in the health system in order to use social participation.…”
Section: Discussionmentioning
confidence: 99%